Reproductive Timing, Education, and Fertility Outcomes: Evidence from the Danuwar Community in Nepal - Devkota , Bijaya Mani; Bohara, Pradeep Kumar (Innovative Research Journal, 2025)
Nepal has practiced a high fertility rate drop and marginalized and indigenous groups are more fertile and reproduce earlier interaction of reproductive timing and socio-economic elements. The Fertility was measured by cross-sectional survey in terms of a quantitative survey of the 289 Women of Danuwar in Lalitpur District (Mean fertility) in terms of Fertility Knowledge (FK), and Children Ever Born (CEB) as a measure of the Total fertility rate (TFR), descriptive statistics, ANOVA, multiple linear regression to determine the effects of education, employment, child mortality experience, singulate mean age at marriage (SMAM) and timing of childbearing. TFR was estimated and the socio-demographic variation was large and was 2.41. The factors associated with increased fertility included low education, not part of the working population, lost children, married young and the birth spacing was low. The regression equation was also significant (R2 = 0.153; p < 0.01). The reproduction behavior, education, child survival, and economic participation determine fertility of Danuwar women as a transitory period. The absence of equitable improvement of fertility and better reproduction health among the marginalized groups in Nepal requires late marriage, increased female involvement in the labor force, better education and better child-survival programs.